Innovation And Community Empowerment: Strengthening The Regional Entrepreneurship Literacy Kiosk Program In The City Of Bandung - Dwi Oktaviani Sholikhah; Septiana dwiputrianti; Muhamad Nur Afandi; Hye Kyoung Lee (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity is motivated by the importance of literacy as a social capability that is not limited to reading and writing skills, but also serves as a means of improving welfare through the development of entrepreneurship based on local potential. The Kios Literasi Kewirausahaan Kewilayahan (KLIK) Program in Bandung City is designed as a community empowerment innovation that integrates literacy strengthening and MSME development through a participatory and practice-based approach. The objective of this program is to enhance the capacity of program managers, strengthen community participation, and optimize local economic potential through MSME Start-Up activities and the KLIK Festival. The implementation method is carried out through coordination, mentoring, and training conducted by the local government together with the community service team. Community members participate by presenting and introducing MSME products at the KLIK Festival, which is attended by approximately 30–50 participants from various urban villages. Data analysis is conducted using descriptive qualitative and quantitative approaches through observation, interviews, and pre-test and post-test assessments to measure changes in program managers’ capacity. The results show a significant improvement in managerial competencies, particularly in MSME Start-Up management and the implementation of the KLIK Festival. In addition, cross-regional coordination strengthens community involvement in MSME product promotion. These findings indicate that the integration of literacy and entrepreneurship has a tangible impact on strengthening local capacity and community economic empowerment. As concrete outputs, the program produced strengthened MSME promotional activities, improved managerial performance of program implementers, enhanced inter-regional coordination mechanisms, and increased community readiness in developing and marketing local products. Therefore, the KLIK Program is proven to be an effective and sustainable literacy-based community empowerment model.